2018
DOI: 10.1177/0017896918816735
|View full text |Cite
|
Sign up to set email alerts
|

The Food Doctors: A pilot study to connect urban children and medical students using nutrition education

Abstract: Background: Children in the USA face increasing nutrition-related health risks, including obesity rates of 16.9% – a figure that has more than tripled over the past four decades. Nutrition education is beneficial to improve children’s health through obesity prevention and the promotion of healthy habits, and the elementary school years are a key time to implement health education interventions. Objective: To develop a medical student created and operated nutrition education intervention for urban underserved e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Other interventions integrated a component of discussion and information sharing within their didactic classroom lessons. For example, “The Food Doctors program” included a “discussion about a popular food estimated to be familiar to all participants” in their curriculum 49 . Several studies reported using game‐based food and nutrition education, which required students to play and compete with each other 50‐55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other interventions integrated a component of discussion and information sharing within their didactic classroom lessons. For example, “The Food Doctors program” included a “discussion about a popular food estimated to be familiar to all participants” in their curriculum 49 . Several studies reported using game‐based food and nutrition education, which required students to play and compete with each other 50‐55 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, ''The Food Doctors program'' included a ''discussion about a popular food estimated to be familiar to all participants'' in their curriculum. 49 Several studies reported using gamebased food and nutrition education, which required students to play and compete with each other. [50][51][52][53][54][55] Furthermore, intervention descriptions of peer-topeer or teacher-to-student role-modeling of healthy eating behaviors were evidence of nonverbal communication of FL messages.…”
Section: Intervention Alignment With Food Literacy Levelsmentioning
confidence: 99%
“…All student and parent surveys were anonymous and included no personal identifiers. To learn more about the TFD program, please refer to Johnston et al 9 …”
Section: Methodsmentioning
confidence: 99%
“…Feedback from students participating in the Food Doctors (TFD) was the basis for this study. TFD is an elementary school nutrition education program administered by medical students at the Medical College of Wisconsin and serves low socioeconomic and underserved communities in Milwaukee, WI 9 . TFD delivers a 3‐lesson curriculum to third‐grade classes at two elementary schools – St. Marcus Lutheran School (SML) and Milwaukee Academy of Science (MAS).…”
mentioning
confidence: 99%
“…In one instance, a fellowship graduate (DA) who joined the MCW faculty mentored a medical student through development of a school-based nutrition education project entitled Food Doctors. 24 He served as the student's advisor through his family medicine residency, while engaging subsequent cohorts of student leaders to sustain the Food Doctors project. The student ultimately joined the department's faculty and they are now colleagues.…”
Section: Bland Et Al Successful Faculty In Academic Medicine: Essentialmentioning
confidence: 99%